2012
DOI: 10.1080/07373937.2012.710692
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cracking Behavior and Milling Quality of Selected Australian Rice Varieties Due to Postdrying Annealing and Subsequent Storage

Abstract: This study investigated the effect of drying temperatures, annealing regimes, and storage conditions on the level of rice kernel fissuring, mechanical strength, and head rice yield of three Australiangrown rice varieties, namely, Kyeema (long grain), Amaroo, and Reiziq (medium grains). Paddy samples were dried at 40, 60, and 80 C and then annealed for 0, 40, 80, and 120 min at the same drying temperature. It was found that annealing slightly improved the head rice yield with an increase in stiffness of rice ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It was also found that the lower molecular weight polypeptide decreased with the increase of storage time, while the higher molecular weight polypeptide increased (Park et al, 2012;Chrastil, 1990). More importantly, the content of acetic acid soluble protein in milled rice decreased during 7 years of storage (Bolling et al, 1977;Bolling et al, 1978;Mangrauthia et al, 2017). During the aging process, the protein content of rice grain changed slightly, but the soluble nitrogen decreased continuously.…”
Section: Effects Of Rice Aging On Physicochemical Properties Of Storamentioning
confidence: 89%
“…It was also found that the lower molecular weight polypeptide decreased with the increase of storage time, while the higher molecular weight polypeptide increased (Park et al, 2012;Chrastil, 1990). More importantly, the content of acetic acid soluble protein in milled rice decreased during 7 years of storage (Bolling et al, 1977;Bolling et al, 1978;Mangrauthia et al, 2017). During the aging process, the protein content of rice grain changed slightly, but the soluble nitrogen decreased continuously.…”
Section: Effects Of Rice Aging On Physicochemical Properties Of Storamentioning
confidence: 89%
“…Golmohammadi et al [40] and Truong et al [41] reported that the tempering could reduce the rice fissuring significantly and subsequently improve the mechanical properties of rice such as hardness and toughness. However, although the tempering can prevent the rice fissuring, but the termination of drying at 30 s would be difficult if the dryer was operated continuously since the residence time in this dryer, approximately 3 or 4 minutes, was relatively long in the commercial dryer.…”
Section: Stresses Inside Gbr Kernelmentioning
confidence: 98%
“…Annealing may be conducted as a single-or multistep process , Nakazawa & Wang 2003, Shi 2008, Gomand et al 2012; in a dual process prior to or following HMT (Adebowale et al 2009;Chung et al 2009aChung et al , 2010; in situ within cereal grains and potato tubers during cultivation, processing, and/or storage Tester et al 1999Tester et al , 2005Genkina et al 2004;Kiseleva et al 2004;Piecyk et al 2009;Truong et al 2012); within whole-tissue flours (Zhou et al 2003(Zhou et al , 2010Cham & Suwannaporn 2010;Chung et al 2012a,b); prior to or following chemical modification (Song et al 2011, Majzoobi et al 2012; following acid hydrolysis (Brumovsky & Thompson 2001, Lin et al 2009); after starch fermentation (Gomes et al 2010); or in conjunction with nixtamalization (Figueroa et al 2013a,b). Annealed flours have been evaluated for their ability to improve the characteristics and properties of various noodles (Hormdok & Noomhorm 2007, Cham & Suwannaporn 2010).…”
Section: Other Annealing Treatmentsmentioning
confidence: 99%